A Nosocomial Outbreak of Community-Associated Methicillin-Resistant Staphylococcus aureus among Healthy Newborns and Postpartum Mothers - Andrea Saunders; Linda Panaro; Allison McGeer; Alana Rosenthal; Diane White; Barbara M Willey; Denise Gravel; Erika Bontovics; Barbara Yaffe; Kevin Katz (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) has increasingly been isolated from individuals with no predisposing risk factors; however, such strains have rarely been linked to outbreaks in the hospital setting. The present study describes the investigation of an outbreak of CA-MRSA that occurred in the maternal-newborn unit of a large community teaching hospital in Toronto, Ontario.